Drag-based swimmer robot II - Chee, Zhong Sheng (Nanyang Technological University, 2023)
Traditional underwater robots such as Remotely Operated Underwater Vehicles (ROVs) and Autonomous Underwater Vehicles (AUVs) have been used for a wide range of applications ranging from military operations to marine explorations. However, both types of underwater robots have limitations in navigating through complex environments. Biomimicry, the study of biological organisms to incorporate their desirable characteristics into technological design solutions, has shown potential in developing nature-inspired swimmer robots such as fishes, dolphins, and manta rays. However, such robots lack the versatility required for narrow underwater space exploration. This project focuses on the Antarctic krill, which are highly manoeuvrable and efficient swimmers, as an inspiration for developing underwater robots intended for more flexible underwater operations. The objective of this project is to design and fabricate a swimmer robot that mimics the swimming motion of krill and evaluate the performance of drag-based swimming in robots. In this project, a robot modelled after the krill was designed and fabricated using 3D printing. The robot's movements were programmed using Arduino to achieve oscillatory motion that matches the swim cycle of krill at a frequency of 1.11Hz. Guided displacement tests were conducted to evaluate the robot's performance, which showed that the robot could emulate krill movement underwater and generate forward propulsion. To the best of the author’s knowledge, there is currently no research that quantitatively measures the propulsive capabilities of a krill-inspired robot. The final test results showed that the robot was able to travel an average of 10mm/min atop a pair of rulers used to constrain the motion of the robot and to measure the displacement.